"It's a generosity loop": Religious and spiritual motivations of volunteers who glean produce to reduce food insecurity. Issue 4 (2nd October 2017) - Dennis, Mary Kate; Scanlon, Edward T.; Sellon, Alicia M.
ABSTRACT: Food insecurity is a common social issue and households look to assistance from food pantries, which often have difficulty supplying fresh or nutritious food. A substantial amount of produce is left in the fields, which can be collected through gleaning. In a focus group with volunteer gleaners at a faith-based nonprofit organization that attempts to fill the gaps of food insecurity, the motivations, challenges, and benefits of volunteering were examined. Volunteering in gleaning generated a sense of collective purpose and community; it addressed deeply held religious and spiritual impulses; and it puts volunteers directly in contact with nature.